Maraknya Catcalling (Pelecehan Verbal) Ditinjau dari Perspektif Hukum Pidana dan HAM - Mochammad Alfin Ramdhan; Ismail Marzuki; Bagus Wibowo; Zainal Arifin; Rinni Puspitasari (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
Sexual harassment is an action or behavior that contains sexual elements that the victim does not want. Sexual harassment itself has a vast scope, for example in the form of writing, both physical and non-physical (poking, touching, caressing, hugging, and so on), displaying something that contains pornographic/dirty elements, indecent assault, or coercion. One example that is currently widespread is catcalling, namely verbal sexual harassment against women. Recently, it has been in the spotlight because of the many unpleasant incidents that happen to women. Until now, catcalling itself is still considered a common thing in society so that the perpetrators themselves are never given a deterrent effect, even though catcalling can also include verbal harassment which can be interpreted as the act of saying pornographic/sexual or flirtatious or itchy words. This sassy nature causes feelings of discomfort in someone who is the victim of harassment, even if it is just a joke. The research method used is a normative juridical and literature study, by analyzing a legal problem through statutory regulations, literature, and other reference materials. The formulation of the problem found in this research is firstly, does catcalling fulfill the elements of a criminal act of sexual harassment in terms of criminal law and human rights (HAM) in Indonesia and secondly, what is the purpose of this legal trap? perpetrators of catcalling crimes.